EDUCATION ON THE RISKS OF USING HAZARDOUS ADDITIVES IN SNACKS FOR STUDENTS AT MARGAHAYU II ELEMENTARY SCHOOL IN BEKASI CITY - Annisa Amalia; Sari Defi Okzelia; Fajar Amirullah; Ristiana Kusumawinahyu; Dina Wahyu Pratiwi; Siti Mar'atun (Faculty of Vocational Studies, Universitas Airlangga, 2021)
Background: Food safety and quality studied by BPOM Indonesia in 2008-2011 showed that around 48% of hazardous substances are found in snacks of elementary school children. Throughout 2012, this percentage increased to 66.7%. Cases of chemical contamination that are still frequently found are the use of additives such as formaldehyde, borax and rhodamine B. Lack of supervision and education to children causes the possibility of consuming dangerous foods to be large thus increasing the risk to health. Objective: This activity was conducted to improve understanding, knowledge and awareness of the community, especially students about the risk of using hazardous additives in snacks. Method: Stages of community service activities include: (1) Pre-activity; (2) Implementation; and (3) Evaluation. The method used was a combination of community education and demonstration. In the core of the activity, there were three sub-activities implemented. Results: An increase in understanding hazardous additives in snacks for students was achieved. It was known that the sample circulating around school did not contain rhodamine B and borax. Futhermore, students can practice one simple way to implement clean and healthy living. Conclusion: The program provided an increase in understanding and awareness of hazardous additives in snacks for students.